Assessment of Stress Levels and Coping Strategies Among Students at a Dental School in Southern California - Dima Ibnian; Axel Barba; Sara Mojtahedi; Debra Friesen; Udochukwu Oyoyo; So Ran Kwon (Journal of the California Dental Association, 2025)
Objective The purpose of this study is to assess stress levels among dental students at a dental school in Southern California and identify major stressors and common coping strategies utilized by students.Materials and Methods A cross-sectional survey was distributed to dental students from the classes of 2025–2028 (N = 464). The 32-item survey included demographics, Dental Environment Stress (DES) questionnaire, and questions on stress coping strategies. The DES questionnaire rates 24 academic, clinical, social, and personal stressors on a five-point Likert scale (1 = not stressful to 5 = highly stressful), yielding total scores from 24 to 120. Quantitative data were analyzed using descriptive statistics, t-tests, and correlation analyses. Open-ended responses were thematically analyzed to identify perceived needs for institutional support.Results A total of 218 students responded (response rate: 46.9%). Mean DES score was 55.5 (SD = 18.7), with no statistically significant difference between males and females (p = 0.090). Top stressors included examinations and grades (mean = 3.5), patient care responsibilities (mean = 3.1) and amount of classwork (mean = 3.0). Common coping strategies were socializing (73.9%), hobbies (66.1%), and physical activity (63.8%). Higher use of coping strategies was significantly associated with higher stress (r = 0.562, p < 0.001). Students who perceived institutional resources more favorably also reported lower stress levels (r = −0.272, p < 0.001). Open-ended responses emphasized the need for free food and snacks, mental health services, academic flexibility, and social support.Conclusion Dental students experience moderate to high stress, primarily from academic and clinical sources. While personal coping strategies help reduce stress, students also identified a need for enhanced institutional support.Practical Implications Enhancing access to institutional mental health resources and fostering supportive environments could not only improve students’ immediate well-being but also prepare them for long-term success and emotional resilience in their professional careers.